DISTRIBUTION AND CIRCULATION OF CHROMIUM (Cr) ANDCADMIUM (Cd) METALS IN TIGRIS RIVER - Al-Azzawi, Mohammed (Iraqi Journal of Science, 2024)
The distribution and circulation of chromium and Cadmium in Tigris river wereestimated over a period (2001–2002). Significant difference was observed in theconcentration of these metals in any component of the homomorph model in studiedarea. Result obtained were in agreement with those reported for heavy metalconcentrations in other polluted ecosystems. All components of the ecosystem wereinvolved in the circulation of the heavy metals either by accumulation orconcentrations processes.